"A New Ethnology": The Legal Expansion of Whiteness under Early Jim Crow. (August 2021) - Pollak, Benjamin H.
Abstract : The segregation laws known as "Jim Crow" are often understood as legislative efforts to promote White supremacy by shielding White southerners from contact with other races. This was not the case, however. By analyzing early railway segregation laws–in particular, the 1890 Louisiana law that was challenged in Plessy v. Ferguson–this article shows that the first post-Reconstruction segregations laws used an expansive definition of the "white race" as everyone who was not Black. In short, White purity and separation were the pretext, not the purpose, of early Jim Crow laws. Instead, the structure of legal segregation was initially determined by White, Democratic legislators' efforts to isolate and subjugate Black Americans by reinstating the racial logic of slavery, which had divided the world into Black people and everyone else. To achieve this end, White supremacist lawmakers framed laws that strategically integrated "white" train cars, all the while claiming the laws did the opposite.